Eating disorder symptoms and quality of life: Where should clinicians place their focus in severe and enduring anorexia nervosa?. Issue 1 (22nd July 2014) - Bamford, Bryony; Barras, Christina; Sly, Richard; Stiles‐Shields, Colleen; Touyz, Stephen; Le Grange, Daniel; Hay, Phillipa; Crosby, Ross; Lacey, Hubert
ABSTRACT Objective The aim of this study was to examine the relationship between quality of life (QoL), weight, and eating disorder symptoms across treatment in individuals with severe and enduring anorexia nervosa (SE‐AN). Method Participants were 63 adult females with SE‐AN presenting to an outpatient, multisite randomized clinical trial. QoL was assessed using three well‐validated QoL questionnaire measures, the EDQOL, SF‐12, and WSAS. Participants' weight and severity of symptoms was assessed by Eating Disorder Examination (EDE) and weekly BMI change. Results Predictors of QoL were evaluated in the context of concurrent, prospective, 1 and lagged mixed‐effects models. Changes in both BMI and EDE were found to significantly affect current and future QoL ratings. Discussion Findings suggest that improvements in QoL may be dependent on symptom change and weight gain. Treatments seeking solely to improve QoL may be unlikely to produce lasting change and clinicians should maintain a focus on weight and behavioral symptoms as much as on improvements in QoL. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:133–138)